158 Effect of fumonisin-contaminated corn on growth performance of 9- to 28-kg nursery pigs - Rao, Zhong-Xing (J Anim Sci, 2020)
A total of 350 pigs (241×600; DNA, Columbus, NE; initially 8.9 kg) were used in a 28-d study to determine the effect of fumonisin-contaminated corn on growth performance of nursery pigs. Dietary treatments consisted of fumonisin-contaminated corn blended with low fumonisin corn to provide analyzed toxin (FB1 + FB2) levels in the final diet of 7.2, 14.7, 21.9, 32.7, and 35.1 ppm. There were 5 pigs per pen and 14 pens per treatment. Pens were assigned to treatments in a randomized complete block design with initial weight as the blocking factor. Data were analyzed using lme package in R program with pen as the experimental unit. From d 0 to 28, increasing fumonisin decreased (linear, P< 0.05) ADG, ADFI, G:F, and final BW. Although responses tested linear, the greatest reduction in ADG and G:F was observed in pigs fed 32.7 and 35.1 ppm of fumonisin. Increasing fumonisin increased serum sphinganine to sphingosine (Sa:So) ratios (linear, P< 0.001) on day 14 and 28. Serum Sa:So ratio appears to be a useful biomarker indicating fumonisin intoxication. These results suggest that for 9- to 28-kg nursery pigs, diets containing 32 ppm of fumonisin or greater decreased growth performance and increased serum Sa:So ratio. Further research is warranted to determine the effects of fumonisin concentrations between 22 and 32 ppm. [Image: see text]